Enjeux d’hier dans les découpages territoriaux d’aujourd’hui : les Grimaldi de Monaco et le Carladez (Aveyron-Cantal) - Géraud Cullier de Labadie; Marie Redon (EchoGéo, 2024)
The starting point of this article is Prince Albert II of Monaco's visit to the Carladez district on 14th and 15th May 2014, a district corresponding to the fief fallen to the Grimaldi family's share in 1643 and now straddling Cantal and Aveyron departments and thus the Auvergne and Midi-Pyrénées regions. Through a geo-historical approach, the intention is to understand the meaning of the historic link between the two territories, Monaco and the Carladez, both for the Principality and for the inhabitants of the communes concerned: does the former fief still make sense as a territorial entity despite its having been split up? What makes legitimate a territorial carving when the Republic's internal borders are being questioned (proposal of a territorial reform to redraw the map of regions in June 2014)? A comparison chart showing how marked the differences are between the two areas is followed by an analysis of the construction of the relations between the two territories in the course of their common history. The setting up of the administrative boundaries after the French Revolution leads to question the relativity of the idea of distance over time as well as the continued existence of the fief as a tourist destination. The article aims to show that the symbolic and memorial issues are all the greater in the Carladez because they set apart a territory of the Massif Central and establish it as a destination with an aura of princely prestige. As for the Principality of Monaco, it is emblematic of the spatial logic according to which the exception is worth more than territorial continuity.